EKSISTENSI MAHASISWI DALAM BERORGANISASI DI LINGKUNGAN FAKULTAS PENDIDIKAN ILMU PENGETAHUAN SOSIAL UNIVERSITAS PENDIDIKAN INDONESIA - Mustofa, Zaenal (Universitas Pendidikan Indonesia, 2016)
This study is based on the domination of men in a strategic position in organization at the Faculty of Social Science Education. This research is aimed at give a comprehensive depiction about women existence in organization. The research utilizes descriptive method with qualitative approach. Women and men existence in organization is considered equal; however in the distribution of tasks, women’ stereotype can’t be completely detached. Women’s motivation is gain experiences to support their academic and social life. Women accesibility in holding a strategic position is open. However, to hold a leading role, there is an influence from the perspective of men’s masculinity. The problems occurred to women in organization are biological factor (menstruation), limited access and conflict. To release the biological factor, women consume the pain killer, while to solve the problem of limited acess they coordinate and cooperate and to solve the conflict, they discuss with the people related conflict to get mutual agreement.